2019
DOI: 10.1371/journal.pone.0226756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of hypertension and sodium intake in Zhejiang Province, China: A cross-sectional survey in 2017

Abstract: BackgroundIn recent decades, hypertension has become a popular public health problem in China. In 2017, a cross-sectional survey about hypertension and sodium intake measured by 24-hour (24-h) urine was launched in Zhejiang Province, to provide the basis of the Chinese population to develop a salt reduction intervention and prevention of hypertension strategy.MethodsCross-sectional data were obtained from 7512 participants aged 18 to 69 years in Zhejiang Province of China by complex, multistage sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The reason might be that the average age of our cohort is 64.0 ± 8.3, which is relatively high in correspondence with metabolic disorders, such as serum lipid and serum glucose abnormalities. It is reported that the average blood pressure was higher in population of China's rural area (Du et al, 2019 ). In our study, it might be due to the higher average ages of our cohort or the normal diet habits in the countryside of northern China, which consisted of high salt, high oil recipe.…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be that the average age of our cohort is 64.0 ± 8.3, which is relatively high in correspondence with metabolic disorders, such as serum lipid and serum glucose abnormalities. It is reported that the average blood pressure was higher in population of China's rural area (Du et al, 2019 ). In our study, it might be due to the higher average ages of our cohort or the normal diet habits in the countryside of northern China, which consisted of high salt, high oil recipe.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, a provincially representative sample of 7512 residents gave informed consent and participated in the project with a complete database, of which 1424 responders collected complete 24-h urine to assess the overall sodium intake. Methods for sample size calculation and sample selection are described in detail elsewhere 18 . The permission protocol to undertake the SRHPP and written participant consent were obtained from the China Centers for Disease Control and Prevention (CDC) and all participants, respectively.…”
mentioning
confidence: 99%
“…The prevalence rate in 2017 had increased greatly when compared with that of 22.6% in 2013 (Wang et al, 2013). This change may be caused by unhealthy lifestyle, such as diet and limited exercise (Du et al, 2019). The establishment of the new Rural Cooperative Medical System intended to address the health needs within most of the country's rural households (Chen et al, 2016) did not decline the prevalence of HTN.…”
Section: Introductionmentioning
confidence: 99%
“…HTN in China is still in a state of "one high" (high prevalence) and "three lows" (low awareness rate, low treatment rate, low control rate). Zhejiang Province, one of the richest provinces in mainland China, had 30.41% prevalence rate for HTN and 31.65% in rural area in 2017 (Du et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation